Once More on the Word jeste (= still, yet) - Nejedly, Petr (Bohemica Olomucensia, 2016)
The article compares the syntactic-semantic analysis of the lexical unit jeste (still, yet), made by Miroslav Komarek in 1958, with lexicographical treatment of the same lexeme in a Czech diachronic dictionary. Komarek works with two basic oppositions: his description starts on the position of the lexeme in syntactic structure of the sentence (according to the fact if the lexeme is construed with predicate or with some other valency complement), further, he distinguishes between meanings expressing contrastive-confrontational relationship (discrepancy in supposed temporal limits of the action) and meanings expressing continuity of the action (connecting, multiplying the same phenomena). On the other hand, lexicology is based on the etymology (primarily, the lexeme expresses relation to some spatial limit denoting common heading for something) and on the semantic development of the lexeme; lexicology considers temporal modification of the action as a starting point (its relationship to the supposed temporal limit): the lexeme expresses discrepancy in the usual limit primarily, secondarily, its exceeding which leads to another limit and is realized as a connection of another phase of the action until the full realization of the action. Therefore, the Old Czech lexeme jeste takes comparative minimally. The syntactic position of the lexeme does not make any difference. Finally, the author claims the grammarian Komarek has precisely grasped basic semantic features of the lexeme which are also crucial for the lexical analysis. However, the lexicology does not need to study either the bond on the predicate, or the criterion of temporal relations, it follows semantic shifts based on different semantic features instead. Nevertheless, Komarek's analysis is still of a great importance for the lexicology and it is possible to exploit it in lexicographical treatment.
Keywords: Miroslav Komarek; lexical unit jeste (= still; yet); grammatical analysis; lexicological analysis; lexical meaning